1986
DOI: 10.1002/ajh.2830210102
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of platelets according to size: Functional and biochemical characteristics

Abstract: The functional and biochemical heterogeneity of platelets has been studied using graded differential centrifugation to fractionate human platelets according to size while maintaining their morphological and functional integrity as indicated by scanning electron microscopy and content of beta-thromboglobulin. Aggregation kinetics were studied by both optical and quenched-flow methods involving single-particle counting. Large platelets were significantly more sensitive to ADP, but aggregated less rapidly than sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Leithner et al [5] have observed the aggregates on dialyzer membrane, whereas Guzzo et al [3] have found increase levels p-thromboglobulin, in hemodialysed patients, a marker of platelet activation and destruction in vivo. Because greater plate lets with higher numbers of dense granules are more sensitive to activation than smaller ones [1] our results may suggest that this type of platelets is likely eliminated first from the circulation after contact w'ith dialyzer mem branes.…”
Section: Discussionmentioning
confidence: 79%
“…Leithner et al [5] have observed the aggregates on dialyzer membrane, whereas Guzzo et al [3] have found increase levels p-thromboglobulin, in hemodialysed patients, a marker of platelet activation and destruction in vivo. Because greater plate lets with higher numbers of dense granules are more sensitive to activation than smaller ones [1] our results may suggest that this type of platelets is likely eliminated first from the circulation after contact w'ith dialyzer mem branes.…”
Section: Discussionmentioning
confidence: 79%
“…These small cells contain the lowest specific content of glycogen, an observation consistent with increased resting levels of cytosolic calcium and a more active phosphorylase kinase. 33 In essential hypertension there may be a shift in the nature of the platelet population, perhaps as a result of an alteration at the precursor level, or an abnormal conditioning during circulation. We might have predicted an alteration in platelet size, 3033 but we found no difference (Table 4) between hypertensive and normotensive groups.…”
Section: Platelet Calcium and Blood Pressurementioning
confidence: 99%
“…45 The question of heterogeneity of platelet size and function has interested investigators for some time. Although there are clear differences in function and biochemical characteristics, 33 it is generally agreed that platelet size does not correlate with platelet age. 33 -4647 A number of mechanisms, confirmed and presumptive, responsible for elevated platelet [Ca 2+ ]; in hypertension have been proposed.…”
Section: Platelet Calcium and Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that platelets adhere to the vessel wall, as they are stimulated by being exposed to injured endothelium [ 11. There are studies indicating that only a small part of blood platelets is actively involved in the platelet-vessel wall interaction [ 2 , 3 ] . With respect to heterogeneous morphological and functional characteristics, the existence of different subpopulations of platelets was proposed [4][5][6][7]. However, little is known as to whether the adhesion features of platelets and the related biochemical properties are different in such subpopulations.…”
Section: Introductionmentioning
confidence: 99%